Aerobic fitness and lifestyle with non-exercise physical activity in adults with cerebral palsy - Ayako Satonaka; Nobuharu Suzuki (Japanese Society of Physical Fitness and Sports Medicine, 2018)
This review article explores how to keep individuals with cerebral palsy healthy all their life. Many of these individuals live very sedentary lives, remaining at home after leaving school or completing childhood rehabilitation programs. Aerobic fitness in such individuals is known to decline rapidly in adulthood. Therefore, in order to keep aerobic fitness from falling into decline, the physical activities and aerobic fitness of these individuals must be appropriately and rigorously managed. The authors recently showed the validity of submaximal exercise testing and provided some findings that would contribute to improving aerobic fitness in these individuals. These studies indicate that even NEAT (Non-Exercise Activity Thermogenesis) or brief and frequent daily physical activity, rather than just conventional exercises or sports, could improve aerobic fitness. However, other studies recommend that these individuals engage in exercises or sports that they may not be interested in or that require facilities or occasions that are inaccessible. In conclusion, in addition to a standard exercise regimen, realistic and tangible interventions for daily physical activities need to be made available to individuals with cerebral palsy.